(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Type 1 Diabetes (T1D) has historically been regarded as a sudden and unpredictable autoimmune condition — often first recognized only after the onset of symptoms like excessive thirst, frequent urination, unexplained weight loss, and, in many cases, a life-threatening episode of diabetic ketoacidosis (DKA). By the time a diagnosis is made, significant and often irreversible damage to the insulin-producing beta cells of the pancreas has already occurred. However, this traditional, reactive approach is rapidly evolving. Advances in genetics, immunology, and early screening technologies are reshaping our understanding of how T1D develops and how it might be prevented. Researchers now recognize that T1D follows a staged progression, starting silently years before clinical symptoms emerge. This paradigm shift—from waiting for symptoms to identifying and tracking disease risk early—has opened promising new pathways for prediction, prevention, and even delay of disease onset.